Analisis Beban Ekonomi dan Dampak Karena Tuberculosis terhadap Kesejateraan di Kota Bengkkulu - Susilo Wulan (CHMK HEALTH JOURNAL, 2020)
Tuberculosis (TB) disease placed tremendous burdens on patients, families, communities, and government budgets. In addition to the work productivity loss, most profound effect declineed in level of well-being even impoverishment. The purpose of this study was to analyze the economic burden and impact of Tuberculosis disease in patients and household members. It is a retrospective descriptive study with cross sectional study design. Study population was TB patients who were treated at all Health City Center in Bengkulu City with the sampling technique using a probability proportional to size a number of 71 patients. The estimated total economic burden due to TB disease in Bengkulu City was IDR 7,215,200 up to IDR 12,970,200, - or 28.28% -50.84% of the average household income. The most dominant component of cost was the indirect cost of IDR 5,135,300, - or 20.13% of the average household income, followed by the direct cost of IDR 2,080,600, - (8.15%) of the average household income. 87.3% average monthly income decreased due to TB. The effect of income decline led to 19% of high income households falling in the low income group. Due to the decrease in income, 43.7% of households changed their consumption patterns by reallocating in consumption. Patients with low-income groups spent 14% of household income on TB treatment. To reduce the risk of medical costs and the uncertainty of medical costs, it is necessary to establish the pathnersip with the private sector, the need for public funding in the form of pre-payment mechanism and health policy in protecting the household from all costs due to TB disease.